The impossibility of mortality evaluation of skin cancer screening in Germany based on health insurance data: a case–control study. (September 2022) - Stang, Andreas; Schuldt, Katrin; Trocchi, Pietro; Neusser, Silke; Speckemeier, Christian; Pahmeier, Kathrin; Wasem, Jürgen; Lax, Hildegard; Nonnemacher, Michael
Abstract: Background: The aim of this paper was to perform a mortality evaluation of skin cancer screening (SCS) in Germany using General Local Health Insurance Fund (AOK) data. Methods: AOK-insured men and women aged 35–99 years who died of cutaneous malignant melanoma in 2015–2016 were identified. Controls were AOK-insured people who survived to the end of each case's year of death. For each case, 10 controls were matched. The SCS history of each individual was reconstructed using the billing codes 01745 and 01746. Results: In total, 1037 melanoma deaths and 10, 370 controls were included. Cumulative SCS prevalence increased among controls over calendar years, as expected (males and females, 2009: 13.5% and 12.5%; 2015: 52.1% and 55.1%). In contrast, among cases, cumulative SCS prevalence was already high in 2009 and did not show a monotonic increase over the years of diagnosis. Of the 1037 melanoma deaths, 224 (21.6%) had at least one SCS settled in the 12 months after diagnosis. Discussion: A mortality evaluation with health insurance data alone is not possible because SCS billing codes are not only used for real SCS but also for occasion-related diagnostic work-up of abnormal skin findings. A mortality evaluation with health insurance data requires an individual linking with data of the screening physician and the cancer registries. Highlights: The German skin cancer screening program was started in August 2008. To date, no mortality evaluation has taken place. Using health insurance data, we conducted a case–control study. Health insurance data on skin cancer screening in Germany are biased. Billing codes for screening are also used for diagnostic work-up of skin cancer.